Amuk: Sindrom Barat dan Pemberontakan Tak Sadar (Analisis Kritis Pergeseran Makna Amuk dalam Lintasan Sejarah) - Aris Fauzan (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2017)
This article begins with the writer's "disquiet" about the massively absorbed word amuk in English (Europe in general). Whereas the original amuk is a word in Javanese Kawi, which can also be found in Malay, Indonesian, and Tagalok. Starting from this background the author further attempts to reveal the meaning and spirit of the times used by society until the adoption of amuk in the European language. In this brief study the author reveals that: first, the amuk that comes from the Javanese kuno language is not merely means to act brutally and wildly unconsciously the culprit, but amuk can also be interpreted with mengunyak or war. Secondly, amuk is adapted in European language because Europeans can not reason when witnessing amuk acts committed by Malays. In the Mindanao region of the Philippines, amok - by Americans - is used to identify juromendo and sabil actions perpetrated by Moros. Third, in the development of amuk serve as a language of psychopathology for those who carry out brutal acts because of mental health. Fourth, wisely European scientists defend the actions of amuk by the Malays because they are depressed and humiliated by the invaders.